Electronic Health Literacy Skills among Medical and Dental Interns at B P Koirala Institute of Health Sciences - Pokharel, Paras K; Budhathoki, Shyam Sundar; Pokharel, Hanoon P (Journal of Nepal Health Research Council, 2017)
Background: Appropriate use of the available electronic resources is important for decision making in health. The useof electronic resources in health care is universal. The study measures the eHealth literacy skills among the medical anddental interns of the B P Koirala Institute of Health Sciences (BPKIHS), Nepal.Methods: Self administered electronic Health Literacy Scale (eHEALS) was used to collect data from 125 medical anddental interns at BPKIHS. The interns represent immediate past medical student and soon to be professional doctor.Results: A quarter of interns are not sure about the usefulness of internet resources for health. The interns have limitedknowledge about right resources in the internet. They are not equipped to tell useful resources from the not-usefulones in the internet.Conclusions: There is a need to pay attention to the eHealth Literacy needs of the interns. Further research may beneeded to generate evidence on what interventions may be specific to meet the ehealth literacy needs of the medicaland dental interns.Keywords: e-Health Literacy; electronic resources in health; health information technology; health literacy in Nepal;health literacy of intern.